Development and evaluation of a patient-centred program for low anterior resection syndrome: protocol for a randomized controlled trial. Issue 5 (30th May 2020) - Garfinkle, Richard; Loiselle, Carmen G; Park, Jason; Fiore Jr, Julio F; Bordeianou, Liliana G; Liberman, A Sender; Morin, Nancy; Faria, Julio; Ghitulescu, Gabriela; Vasilevsky, Carol-Ann; Bhatnagar, Sahir R; Boutros, Marylise
Abstract : Introduction: Low anterior resection syndrome (LARS) is described as disordered bowel function after rectal resection that leads to a detriment in quality of life, and affects the majority of individuals following restorative proctectomy for rectal cancer. The management of LARS includes personalised troubleshooting and effective self-management behaviours. Thus, affected individuals need to be well informed and appropriately engaged in their own LARS management. This manuscript describes the development of a LARS patient-centred programme (LPCP) and the study protocol for its evaluation in a randomised controlled trial. Methods and analysis: This will be a multicentre, randomised, assessor-blind, parallel-groups, pragmatic trial evaluating the impact of an LPCP, consisting of an informational booklet, patient diaries and nurse support, on patient-reported outcomes after restorative proctectomy for rectal cancer. The informational booklet was developed by a multidisciplinary LARS team, and was vetted in a focus group and semistructured interviews involving patients, caregivers, and healthcare professionals. The primary outcome will be global quality of life (QoL), as measured by the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire—Core 30 (QLQ-C30), at 6 months after surgery. The treatment effect on global QoL will be modelled using generalised estimating equations. Secondary outcomes include symptom change, patient activation, bowel function measures, emotional distress, knowledge about LARS and satisfaction with the LPCP. Ethics and dissemination: The Research Ethics Committee (REC) at the Integrated Health and Social Services Network for West-Central Montreal (health network responsible for the Jewish General Hospital) is the overseeing REC for all Quebec sites. They have granted ethical approval (MP-05-2019-1628) for all Quebec hospitals (Jewish General Hospital, McGill University Health Center, CHU de Quebec) and have granted full authorisation to begin research at the Jewish General Hospital. Patient recruitment will not begin at the other Quebec sites until inter-institutional contracts are finalised and feasibility/authorisation for research is granted by their respective REC. The results of this study will be presented at national and international conferences, and a manuscript with results will be submitted for publication in a high-impact peer-reviewed journal. Trial registration number: NCT03828318; Pre-results.